2018
DOI: 10.3390/ma11122343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selective Laser Melting Process Parameters on the Quality of Al Alloy Parts: Powder Characterization, Density, Surface Roughness, and Dimensional Accuracy

Abstract: Additive manufacturing (AM) of high-strength Al alloys promises to enhance the performance of critical components related to various aerospace and automotive applications. The key advantage of AM is its ability to generate lightweight, robust, and complex shapes. However, the characteristics of the as-built parts may represent an obstacle to the satisfaction of the parts’ quality requirements. The current study investigates the influence of selective laser melting (SLM) process parameters on the quality of par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(119 citation statements)
references
References 38 publications
5
92
1
1
Order By: Relevance
“…The energy density and each process parameter are all significant factors affecting mechanical properties [17,18]. The SLMed sample using a lower hatching distance would have a higher ultimate tensile strength (UTS) and yield strength for AlSi10Mg [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy density and each process parameter are all significant factors affecting mechanical properties [17,18]. The SLMed sample using a lower hatching distance would have a higher ultimate tensile strength (UTS) and yield strength for AlSi10Mg [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the most recent studies focusing on optimizing the SLM process parameters [17,18], the laser power reached less than 400 W because of the limitation of equipment. Therefore, a greater range of laser power will be conducive to finding the optimum combination of processing parameters.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33] The effects of process parameters of DLD on microstructure and mechanical properties can be found in previous studies. A great number of publications examine the effects of these process parameters on part quality for selective laser melting (SLM)/ direct metal laser sintering (DMLS) processes.…”
Section: Am Technology Backgroundmentioning
confidence: 97%
“…[84] Copyright 2015, Elsevier. [31] In addition to laser power, the scan speed is equally important, as shown in Figure 11. The properties of a material that has been additively manufactured are determined by the chemical and phase composition, grain size, and more importantly for AM parts the presence of defects such as pores, cracks, and surface roughness.…”
Section: Microstructure Of Am Alloysmentioning
confidence: 99%
“…Various researches were made regarding the proper process parameters definition and it was observed that a number of process variables for AM are generally used to optimize different characteristics, targeting certain properties of the produced material. Typically, the dimensional accuracy, surface quality and other intrinsic properties of SLM parts are related to variable process parameters such as: laser power, scanning speed, scanning strategy, layer thickness, hatch distance [8,9].…”
Section: Introductionmentioning
confidence: 99%